An asset management approach for drainage infrastructure and culverts - Patil, Rahul; Salman, Baris; Bhattachar, Deepak; Salem, Sam; Najafi, Mohammad (Midwest Regional University Transportation Center, 2008)
Drainage infrastructure systems (culvert, storm sewer, outfall and related drainage elements) are mostly buried underground and are in need of special attention in terms of proactive/preventive asset management strategy. Drainage infrastructure systems represent an integral portion of roadway assets that routinely require inspection, maintenance, repair and renewal. Further challenges are the wide geospatial distribution of these infrastructure assets and environmental exposure. There has been considerable research conducted on culverts, but this research mostly looked at the problem from a traditional structural/geotechnical perspective. Asset management procedures for culverts and drainage infrastructure systems are complex issues, and can benefit a great deal from an optimal asset management program that draws from programs pertaining to buried pipes. The first and most important step in an asset management initiative is the establishment of a mechanism for asset inventory and asset conditions in a format compatible with the routine procedures of field operators and inspectors. The first objective of this research project was to develop field protocols and operational business rules for inventory data collection and management and inspection of drainage infrastructure in terms of types of data to be collected, frequency of inspection, and analysis and reporting mechanisms. After review of these protocols by the project oversight committee, a pilot study was conducted to verify the efficiency of their implementation. The condition assessment protocol introduced is useful in evaluating the overall condition of culverts and can be used for decision making regarding the repair, renewal or replacement of culverts. For the second objective of this project, investigators examined the inventory and inspection protocols employed by the Ohio Department of Transportation and developed a decision support platform, which establishes a link between the inspection results and appropriate repair, renewal and replacement procedures. After applying the recommended procedures, the transportation agencies can better track the conditions of culverts thereby reducing the risk of culvert failures.
271 p.
Keywords: Inspection; Inventory; Decision support systems; Drainage structures; Culverts; Condition surveys; Asset management